Behaviour of 6 types of vegetative material for production of flowers and propagation material - Mattos, J.R.; Simão, S.; Braga Jr., R.L.C.; Campos, H.; Moreira, C.S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
Corms of the same cycle, with near weight and size, presented resembling behaviour for production of flowers, corms and cormels. Greater corms, type 1and 2showed better profit of flowers, corms and cormels than others types, decreasing this profit with the reduction of the size of corms per unity planted. In function of planted weight, the smallest units showed better profit.